Organizational Dynamics in Educational Institutions: A PRISMA-Based Systematic Literature Review - Fitriyana, Fitriyana; Damayanti, Erlian Eka; Luthfiyah, Binti; Subandi, Subandi; Syarifudin, Encep (Yayasan Payungi Smart Madani, 2025)
This study aimed to analyze organizational dynamics in educational institutions using organizational theory and concepts, employing a Systematic Literature Review (SLR) approach based on the PRISMA framework. The review aimed to examine the evolution of organizational theories, their application in educational contexts, and their implications for the effectiveness of educational management. Literature searches were conducted using reputable databases, including Scopus, Web of Science, Google Scholar, and Garuda, encompassing publications from 2010 to 2024. The PRISMA stages consisted of identification, screening, eligibility assessment, and inclusion of relevant articles. From the total number of identified studies, selected articles were analyzed thematically to identify patterns, trends, and research gaps. The findings suggest that classical, contemporary, and modern organizational theories complement one another in explaining the dynamics of educational organizations. Systems theory, contingency theory, and learning organization theory emerged as dominant approaches in enhancing effectiveness, adaptability, and innovation in educational institutions. These findings confirm that a comprehensive understanding of organizational theory and concepts is a key factor in managing educational institutions that are responsive to social and technological change.